Modeling optimal grazing management for grassland rehabilitation on the typical steppe a case study in Taipusi Banner, Inner Mongolia, China - Zheng, Yang; Xu, Zhu; Kemp, David; Takahashi, Taro; Jones, Randall (2010)
Grassland degradation is a serious production and environmental problem in China where approximately 90% of available grasslands are being degraded to some degree. Off-site impacts take the form of sandstorms and the negative impacts upon urban centers in terms of human health and damage to infrastructure. On the other hand, on-site impact is exhibited by low livestock productivity from reduced pasture quality. To evaluate optimal grazing management in China's typical steppe regions, the condition of grassland, number of animals, farm income, seasonal conditions and experimental data were included in a bioeconomic model to analyze the public grazing system in Taipusi Banner, Inner Mongolia, China. The model solutions indicate that net farm income can be increased by reducing stocking rates from current levels, as this could result in a combination of an improvement in grassland condition and increased animal productivity. Improved grazing management through reduced grazing intensity in this region has the potential to not only rehabilitate grasslands but increase whole-farm returns from improved livestock productivity.
Keywords: Rehabilitation; Grassland ecology